SEQUENCE STRATIGRAPHY OF PYEONGAN SUPERGROUP (CARBONIFEROUS-PERMIAN), TAEBAEK AREA, MIDEAST KOREA - Lee H.S.; Chough S.K. (My University, 2006)
This study focuses on the sequence stratigraphy of the Pyeongan Supergroup (Carboniferous-Permian), central-eastern Korea. The supergroup consists of about 1700-m-thick siliciclastic deposits, disconformably overlying the Joseon Supergroup (Carabro-Ordovician). The entire succession is represented by thirteen sedimentary facies which can be organized into seven facies associations (FAs) and, in turn, three sequence units. Sequence 1 constitutes FAs 1, 2, 3, and 4. FA 1 consists of conglomerate, sand-stone and shale facies, and is bounded by a sequence boundary (SB 1) at the base. The overlying purple siltstone with interbedded massive sandstone and carbonate grainstone (FA 2) formed on a coastal plain during sea-level rise, which is transitional upward into black shale and patchy bioturbated carbonate packstone (FA 3) of lagoonal environments. The transition from FA 1 to 3 represents relative sea-level rise with small-scale fluctuations, i.e., transgressive systems tract. FA 4 consists of cross-stratified conglomerate and massive sandstone with black shale which prograded over lagoonal area, forming highstand systems tract (HST). Sequence 2 consists of FAs 5 and 6. Sequence boundary (SB 2) occurs at the transition between FAs 4 and 5. FA 5 is characterized by cross-stratified coarse sandstone and purple fine sandstone to siltstone of fluvial plain environments. It represents rapid change in depositional environments from shoreface to fluvial system. FA 6 comprises upward-fining units (massive sandstone to dark gray siltstone), suggestive of restricted bay environments during relative sea-level rise. Due to an abrupt fall in sea level, the basin was closed with thick fluvial deposits (FA7). Sequence 3 comprises planar and trough cross-stratified coarse sandstone and partly bioturbated purple fine sandstone to mudstone (FA 7). The entire succession represents deposition of a second order cycle of sea-level rise and fall during the period between the Carboniferous and the Permian. A reconstructed relative sea-level curve is concordant with eustasy in the Carboniferous, but discordant in the Permian, implying that the influence of local tectonic movements was dominant in the Permian.
Keywords: CARBONIFEROUS; DEPOSITIONAL ENVIRONMENTS; PERMIAN; PYEONGAN SUPERGROUP; SEA-LEVEL CHANGES; SEQUENCE STRATIGRAPHY; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Permian; Палеозой::Пермская